Технологія формування здорової особистості дитини дошкільного віку у взаємодії дошкільного закладу та сім’ї: вимога часу - Семенова, Наталя; Семенов, Олександр; Semenova, Nataliay; Semenov, Oleksandr (Східноєвропейський національний університет імені Лесі Українки, 2015)
У статті представлено психолого-педагогічні основи процесу формування здорової особистості дитини 6-го року життя у процесі педагогічної взаємодії дошкільного навчального закладу і сім’ї. Описано апробовану експериментальну педагогічну технологію формування здорової особистості дитини 6 го року життя у процесі взаємодії дошкільного навчального закладу і сім’ї. Уточнено сутність понять «здорова особистість», «здорова особистість дитини 6-го року життя», «формування здорової особистості дитини 6-го року життя», «взаємодія дошкільного навчального закладу і сім’ї». Розроблено й апробовано експериментальну педагогічну технологію формування здорової особистості дитини 6 го року життя у процесі взаємодії дошкільного навчального закладу і сім’ї. The article presents the psychologicalpedagogical foundations for forming a healthy personality of children between 5 and 6 years of age in the process of pedagogical interaction between preschool education institutions and families and offers an evaluation of the current state of affairs in the area. An experimental pedagogical technology for forming a healthy personality among children between 5 and 6 years of age in the process of interaction between preschool education institutions and families has been developed and tested. The concepts «healthy personality», «healthy personality of a child between 5 and 6 years of age», «forming a healthy personality of a child between 5 and 6 years of age» and «interaction between preschool education institutions and families» have been defined more precisely. The author has developed a system of criteria and indices to evaluate healthy personality levels among children between 5 and 6 years of age. An experimental pedagogical technology for forming a healthy personality among children between 5 and 6 years of age in the process of interaction between preschool education institutions and families has been developed and tested.
Technology of Healthy Formation of Child’s Personality in Preschool Children in Kindergartens Interaction and Family: Requirement of the Time
Keywords: здорова особистість; взаємодія дошкільного навчального закладу і сім’ї; педагогічна технологія; healthy personality; interaction between preschool education institutions and families; pedagogical technology